SISTEM PENDUKUNG KEPUTUSAN PEMERINGKATAN SISWA MENGGUNAKAN METODE SAW(SIMPLE ADDITIVE WEIGTHING) - Lela Nurlaela; Usanto S. (JEIS: Jurnal Elektro dan Informatika Swadharma, 2021)
This study aims to produce a student ranking system design based on the grades obtained by students to assist teachers and principals in determining the ranking of these students in schools. The criteria used are the midterm score with a weight of 30%, the final exam score with a weight of 30%, the report card value of 20%, and the average value of 20%. The method used is a field study by making direct observations to schools and conducting interviews with school principals, homeroom teachers, and administrative staff. The result of the research is a prototype of a web-based student ranking system that produces a student ranking report that counts using the simple additive weighting method.Keywords: student, rank, grade, saw